Gratitude Therapy to Reduce Suicidal Ideation in Adolescents - Pradnyas, Ajeng; Meiyuntariningsih, Tatik (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study is motivated by the observation of adolescents who have suicidal thoughts. Suicidal ideation refers to an experience where the individual feels that his life is useless. The purpose of this study is to reduce suicidal ideation in group members by increasing each group member's awareness of the positive things they still have. The subjects of this study were adolescents in orphanages. This research uses an experimental research design. The data collection technique used in this study is a measurement with BSS (Beck Scale for Suicide Ideation) to measure the severity of suicidal ideation and plans. The results showed that the gratitude technique was quite successful, so people could be aware of the good things that were still owned.